Reformation thought : an introduction - McGrath, Alister E., 1953- (Oxford, UK ; Malden, Mass. : Blackwell Publishers, 1999)
"Reformation Thought is an introductory guide for theology and history students seeking to understand the central ideas of the European Reformation. Based on Dr. McGrath's considerable experience of teaching Reformation studies, this text requires no prior knowledge of Christian theology."--BOOK JACKET
Late medieval religion -- Humanism and the Reformation -- Scholasticism and the Reformation -- The reformers : a biographical introduction -- The doctrine of justification by faith -- The doctrine of predestination -- The return to Scripture -- The doctrine of the sacraments -- The doctrine of the church -- The political thought of the Reformation -- The diffusion of the thought of the Reformation -- The thought of the English Reformation -- The impact of Reformation thought upon history
Includes bibliographical references (p. [317]-324) and index
Keywords: Theology, Doctrinal -- History -- 16th century; Reformation